METODE MULTISENSORI ARTIKULASI TERHADAP KEMAMPUAN MEMBACA MENULIS HURUF AL-QUR’AN PERMULAAN DENGANMODEL AT-TARTIL JILID 1 SISWA TUNARUNGU - MARDIANA, LAILATUL (Jurnal Pendidikan Khusus, 2016)
ABSTRACT   This research had purpose to observe whether there was influence of multisensory articulation method toward the ability of beginning reading-writing Al-Quran letters with At-Tartil model to hearing impairment students in SLB-B Dharma Wanita Sidoarjo. The approach of this research was quantitative descriptive. The research kind was experiment with Single Subject Research (SSR) arrangement of A-B-A design. The research subject was six hearing impairment children in the third class of SLB-B Dharma Wanita Sidoarjo who had difficulty in reading-writing Al-Quran letters at beginning. The time implication research was 14 times meeting with 3 times baseline (A1), 8 times intervention (B), and 3 times repeating baseline (A2). The technique of data collection in this research used technique test and observation. The research result indicated the average score accumulation of baseline phase (A1), it was continued to intervention phase (B), and it was done repeating baseline (A2) to the ability of beginning reading-writing Al-Quran with VY result which had the average baseline score (A1) i.e. 17,3; to intervention phase (B) i.e. 24,25; and to repeating baseline phase (A2) i.e. 30. NB had the average baseline score (A1) i.e. 19,3; to intervention phase (B) i.e. 29,87; and to repeating baseline phase (A2) i.e 32,67. DN had the average score of baseline (A1) i.e. 20,3; to intervention phase (B) i.e. 24; and to repeating baseline phase (A2) i.e. 30,3. DV had the average score of baseline (A1) i.e. 16,67; to intervention phase (B) i.e. 24,87; and to repeating baseline phase (A2) i.e. 30. FN had the average score baseline (A1) i.e. 18; to intervention phase (B) i.e. 25,12; and repeating baseline phase (A2 i.e. 30. RZ has the average score of baseline (A1) i.e. 20; to intervention phase (B) i.e. 27,62; and repeating baseline phase (A2) i.e. 31,3 so they could be interpreted that the initial ability to baseline phase (A1) could be enhanced through intervention (B) with showing the test result of repeating baseline (A2) which had enhancement. Based on the data it could be concluded that there was influence of multisensory articulation method toward beginning reading-writing Al-Quran letters with At-Tartil chapter 1 to hearing impairment students in SLB-B Dharma Wanita Sidoarjo.   Keywords: Multisensory articulation, reading-writing Al-Quran, At-Tartil model